Pengaruh Lingkungan Kerja Fisik Dan Budaya Organisasi Terhadap Produktivitas Kerja Pada PT. Syajarotun Nuqud Mubarok (Synum) - Dewi, Candra; Krisyanto, Edy (CV. KAMPUSA AKADEMIK PUBLISING, 2025)
Abstrak. This study aims to determine the effect of the physical work environment and organizational culture on work productivity, both partially and simultaneously. This study was conducted using quantitative methods involving employees of PT. Synum as the sample. The technique used to determine the sample in this study was a saturated sample, involving the entire population as a sample of 69 respondents. Data analysis included validity tests, reliability tests, classical assumption tests, regression coefficient tests, correlation coefficient tests, determination coefficient tests, and hypothesis tests. The research results obtained the multiple linear regression equation Y = 4.045 + 0.115 X1 + 0.810 X2, with a coefficient of determination of 0.793, meaning that the Physical Work Environment (X1) and Organizational Culture (X2) influence Work Productivity by 79.3%, with the remaining 0.01% influenced by variables outside the scope of this study. The partial test results for the Physical Work Environment (X1) on Work Productivity (Y) were (9.419 > 1.667) with a significance level of 0.001 < 0.05, thus rejecting H0 and accepting Ha. Therefore, there is a positive and significant partial effect of the Physical Work Environment (X1) on Work Productivity (Y). Furthermore, Organizational Culture (X2) on Work Productivity (Y) is (16.092 > 1.667) with sig. 0.001 < 0.05, thus H0 is rejected and Ha is accepted, indicating that there is a positive and significant partial effect of the Organizational Culture (X2) variable on Work Productivity (Y). Furthermore, in the simultaneous test of the Physical Work Environment (X1) and Organizational Culture (X2) variables on Work Productivity (Y), the result is (130.998 > 3.136) with a significance level of 0.001 < 0.05, thus H0 is rejected and Ha is accepted, indicating that there is a positive and significant simultaneous effect of the Physical Work Environment (X1) and Organizational Culture (X2) variables on Work Productivity (Y). Keywords: Physical Work Environment, Organizational Culture, Work Productivity